(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This scientific article explores the significance of interactive methods in teaching mathematics and their impact on student engagement and learning outcomes. Mathematics education has witnessed a shift from traditional lecture-based approaches to more interactive and student-centered methodologies. This article examines various interactive methods, such as hands-on activities, manipulatives, technology integration, cooperative learning, and problemsolving approaches. It discusses the benefits of incorporating interactive methods in mathematics instruction and provides insights into their effective implementation. The article also addresses potential challenges and offers recommendations for educators to enhance the use of interactive methods in teaching mathematics.